2008
DOI: 10.1007/s00221-007-1263-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rhythmic sensory stimulation (auditory, visual) on gait in Parkinson’s disease patients

Abstract: This study has focused on how sensory stimulation affects gait in Parkinson's disease (PD). The kinematic parameters of gait [cadence, step amplitude, velocity, coefficient of variation of stride time (CV(stride-time)), and the coefficient of variation of the step amplitude (CV(step-amplitude))] were analysed in 25 PD patients and 10 control subjects. Step amplitude, velocity and CV(stride-time) were altered in the patients with PD. However, when kinematic parameters were analysed as a function of disease seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
153
1
16

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 31 publications
12
153
1
16
Order By: Relevance
“…In a study analyzing the gait parameters of Parkinson disease patients provided visual and auditory stimulation, Arias and Cudeiro reported that lower gait velocity, cadence, and step amplitude and higher coefficient of variation in stride time and step amplitude were shown at the lower speed of stimulation 14) . In this study, we found that gait velocity, step length, and stride length increased significantly when visual and auditory stimulation were provided at 150% of patients' normal walking speed compared to stimulation at 50% of their normal walking speed, which is similar to the findings of the abovementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study analyzing the gait parameters of Parkinson disease patients provided visual and auditory stimulation, Arias and Cudeiro reported that lower gait velocity, cadence, and step amplitude and higher coefficient of variation in stride time and step amplitude were shown at the lower speed of stimulation 14) . In this study, we found that gait velocity, step length, and stride length increased significantly when visual and auditory stimulation were provided at 150% of patients' normal walking speed compared to stimulation at 50% of their normal walking speed, which is similar to the findings of the abovementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, and in order to modulate gait velocity, cadence and step length, subjects were asked to walk matching their steps to a metronome, which was set at different percentages of each subject's fast walking cadence (from 50 to 110% FWcadence; order of presentation was randomized). This procedure has been shown tomodulate gait patterns in advance PD without freezing, and in healthy controls (Arias and Cudeiro, 2008); a stimulation condition including a frequency matching PW cadence was also included.…”
Section: Walking Conditionsmentioning
confidence: 99%
“…Therefore these patients were asked to walk at their preferred un-stimulated cadence and also in the presence of a metronome 10 and 20% faster than the PW cadence. Having into account the previous data that shows that auditory stimulation matching PW cadence induces gait patterns with lower cadence tan un-stimulated PW cadence (Arias and Cudeiro, 2008), this condition was included in order to modulate cadence downwards. 12 of the healthy controls performed only this protocol in order to match controls for the different subsets of PD's protocols.…”
Section: Walking Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, FoG is reported as the main cause of falls of PD patients. It has been demonstrated that a rhythmic sensory stimulation can release the involuntary block [2]. Therefore, a non-invasive wearable system able to provide a reliable detection of the FoG in any context, and timely give a sensorial stimulation would be extremely useful for reducing the catastrophic consequences of falls.…”
Section: Introductionmentioning
confidence: 99%